2023
DOI: 10.1055/a-2089-6849
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous lesions after gastric endoscopic submucosal dissection: first assessment of the FAMISH prediction score

Abstract: Background and study aim: Surveillance after gastric endoscopic submucosal dissection (ESD) is recommended for all patients due to the persistent risk of metachronous gastric lesions (MGLs). We aimed to develop and validate a prediction score to estimate MGL risk after ESD for early neoplastic gastric lesions, to define an individualized and cost saving approach. Patients and methods: Clinical predictors and a risk score were derived from meta-analysis data. A retrospective, single centre, cohort study includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
2
1
Order By: Relevance
“…Based on the FAMISH predicting score, the patients were stratified into three risk groups. Notably, the cutoff values for stratification were quite different from those proposed by Rei et al [17], which may be explained by the different patient populations. We also found that MGLs detected in the high-risk group were less likely to be cured with ESD than those detected in the other risk groups, highlighting the need for more intensive surveillance in this subpopulation.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…Based on the FAMISH predicting score, the patients were stratified into three risk groups. Notably, the cutoff values for stratification were quite different from those proposed by Rei et al [17], which may be explained by the different patient populations. We also found that MGLs detected in the high-risk group were less likely to be cured with ESD than those detected in the other risk groups, highlighting the need for more intensive surveillance in this subpopulation.…”
Section: Discussioncontrasting
confidence: 57%
“…The FAMISH predicting score was first developed by Rei et al based on meta-analysis data and was validated in a small cohort of 263 patients who underwent ESD for primary gastric lesions [17]. This score included six clinical predictors: positive family history of gastric cancer (1 point), aged ≥65 years (1 point), male sex (1 point), corpus IM, synchronous gastric lesions (3 points), and persistent H. pylori infection (2 points), with points for each predictor varying from 0 to 3 and a composite score of 0–9.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation